Structural network changes in patients with major depression and schizophrenia treated with electroconvulsive therapy - Wolf, Robert Christian; Nolte, Henrike Maria; Hirjak, Dusan; Hofer, Stefan; Seidl, Ulrich; Depping, Malte S.; Stieltjes, Bram; Maier-Hein, Klaus H.; Sambataro, Fabio; Thomann, Philipp (European neuropsychopharmacology, 2016)
Electroconvulsive therapy (ECT) is one of the most effective treatments in severe and treatment-resistant major depressive disorder (MDD). In schizophrenia (SZ), ECT is frequently considered in drug-resistant cases, as an augmentation of antipsychotic treatment or in cases when rapid symptom relief is indicated. Accumulating neuroimaging evidence suggests modulation of medial temporal lobe and prefrontal cortical regions in MDD by ECT. In SZ, ECT-effects on brain structure have not been systematically investigated so far. In this study, we investigated brain volume in 21 ECT-naïve patients (12 with MDD, 9 with SZ) who received right-sided unilateral ECT. Twenty-one healthy controls were included. Structural magnetic resonance imaging data were acquired before and after ECT. Healthy participants were scanned once. Source-based morphometry was used to investigate modulation of structural networks pre/post ECT. ECT had an impact on distinct structural networks in MDD and SZ. In both MDD and SZ SBM revealed a medial temporal lobe (MTL) network (including hippocampus and parahippocampal cortex) which showed a significant increase after ECT. The increase in MTL network strength was not associated with clinical improvement in either MDD or SZ. In SZ a lateral prefrontal/cingulate cortical network showed a volume increase after ECT, and this effect was accompanied by clinical improvement. These findings provide preliminary evidence for structural network change in response to ECT in MDD and SZ. The data suggest both diagnosis-specific and transdiagnostic ECT-effects on brain volume. In contrast to SZ, in MDD structural network modulation by ECT was not associated with clinical improvement.